Feasibility, acceptability and preliminary effectiveness of patient advocates for improving asthma outcomes in adults. (17th July 2013) - Apter, Andrea J.; Wan, Fei; Reisine, Susan; Bogen, Daniel K.; Rand, Cynthia; Bender, Bruce; Bennett, Ian M.; Gonzalez, Rodalyn; Priolo, Chantel; Sonnad, Seema S.; Bryant-Stephens, Tyra; Ferguson, Monica; et al.
Abstract: Background : Asthmatic adults from low-income urban neighborhoods have inferior health outcomes which in part may be due to barriers accessing care and with patient-provider communication. We adapted a patient advocate (PA) intervention to overcome these barriers. Objective : To conduct a pilot study to assess feasibility, acceptability and preliminary evidence of effectiveness. Methods : A prospective randomized design was employed with mixed methods evaluation. Adults with moderate or severe asthma were randomized to 16 weeks of PA or a minimal intervention (MI) comparison condition. The PA, a non-professional, modeled preparations for a medical visit, attended the visit and confirmed understanding. The PA facilitated scheduling, obtaining insurance coverage and overcoming barriers to implementing medical advice. Outcomes included electronically-monitored inhaled corticosteroid (ICS) adherence, asthma control, quality of life, FEV1, emergency department (ED) visits and hospitalizations. Mixed-effects models guided an intention-to-treat analysis. Results : 100 adults participated: age 47 ± 14 years, 75% female, 71% African–American, 16% white, baseline FEV1 69% ± 18%, 36% experiencing hospitalizations and 56% ED visits for asthma in the prior year. Ninety-three subjects completed all visits; 36 of 53 PA-assigned had a PA visit. Adherence declined significantly in the control ( p  = 0.001) but not significantly in the PA group ( p  = 0.30). Both PA and MI groups demonstrated improved asthma control ( p  = 0.01 in both) and quality of life ( p  = 0.001, p  = 0.004). Hospitalizations and ED visits for asthma did not differ between groups. The observed changes over time tended to favor the PA group, but this study was underpowered to detect differences between groups. Conclusion : The PA intervention was feasible and acceptable and demonstrated potential for improving asthma control and quality of life.